2015
DOI: 10.1002/chem.201503485
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photostability of a Ruthenium(II) Polypyridyl Complex under Highly Oxidizing Aqueous Conditions by Its Partial Inclusion into a Cyclodextrin

Abstract: Abstract:The complex [Ru(bpy)2L] 2+ , where bpy = 2,2'-bipyridine, L = 4-(phenylethynyl)-2,2'-bipyridine, was prepared in its racemic and resolved forms (and . The phenylethynyl unit on the bipyridine for the complex acts as a binding site for -cyclodextrin in water (1:1 complex, K = 3390 M -1 ) or -cyclodextrin (2:1 complex, K1 = 887 M -1 , K2 = 8070 M -1 ). The presence of the cyclodextrin provides partial protection to the complex under light-activated water oxidation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A great variety of inclusion compounds of cyclodextrins with platinum-group metal complexes as guests have been synthesized and used in catalytic processes or bioactivity studies. In 1985 Stoddart and co-workers for the first time used cyclodextrins as encapsulatory vehicles for platinum­(II) complexes. , The authors demonstrated that cyclobutane-1,1-dicarboxylatodiammine–platinum­(II) ([Pt­(NH 3 ) 2 (CBDCA)] forms a 1:1 adduct with α-CD in aqueous solution as well as in the solid state. The adduct is stabilized by N–H···O hydrogen-bonding interactions between the two NH 3 ligands with the secondary hydroxyl groups on α-CD as well as hydrophobic interactions resulting from penetration of the cyclobutane ring of the complex into the α-CD cavity.…”
Section: Inclusion Complexes Of Native Cyclodextrins With Organometal...mentioning
confidence: 99%
“…A great variety of inclusion compounds of cyclodextrins with platinum-group metal complexes as guests have been synthesized and used in catalytic processes or bioactivity studies. In 1985 Stoddart and co-workers for the first time used cyclodextrins as encapsulatory vehicles for platinum­(II) complexes. , The authors demonstrated that cyclobutane-1,1-dicarboxylatodiammine–platinum­(II) ([Pt­(NH 3 ) 2 (CBDCA)] forms a 1:1 adduct with α-CD in aqueous solution as well as in the solid state. The adduct is stabilized by N–H···O hydrogen-bonding interactions between the two NH 3 ligands with the secondary hydroxyl groups on α-CD as well as hydrophobic interactions resulting from penetration of the cyclobutane ring of the complex into the α-CD cavity.…”
Section: Inclusion Complexes Of Native Cyclodextrins With Organometal...mentioning
confidence: 99%
“…platinum(II) anticancer complexes such as carboplatin, 13 metallocene dihalides, [14][15][16][17] aromatic ruthenium complexes, 18 mixed sandwich complexes, 19 and numerous half-sandwich metal carbonyl and cyano complexes. 12,20 Encapsulation can affect the geometry of the guest, 21 its solubility and bioavailability, [22][23][24] thermal stability, 25,26 reactivity, 27,28 photostability, 29 photoluminescence, 30,31 and electrochemical 8,19,32,33 behaviour. These changes can be advantageous for application of OM@CD complexes as catalysts, [34][35][36] metallodrug delivery systems, 9,10,13,16,20,[22][23][24] supramolecular materials for opto-electronics, 37,38 electrochemical biosensors, 39,40 and molecular machines and switches.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays the applications of cyclodextrin-ruthenium supramolecular systems are largely spread across many fields. Examples include molecular devices such as single or polynuclear fluorescence sensors (Zhang et al 2015;Chen et al 2013) and CD-stabilised Ru(II) photosensitizers for dye-sensitized solar cells (Farras et al 2016) or cyclodextrin metallosurfactants (M = Ru(II)) for gene therapy (Lebron et al 2015;Iza et al 2015). In antitumoral chemotherapy, ruthenium complexes make a strong claim as alternatives to platin compounds, for their more versatile ligand-exchange abilities, redox properties (?2 and ?3 oxidation states accessible in vivo) and octahedral geometry (instead of planar four-coordinated Pt) (Bergamo et al 2012).…”
Section: Introductionmentioning
confidence: 99%